Apakah Inflasi Dan Suku Bunga Memengaruhi Profitabilitas Bank Umum Syariah Di Indonesia? - Fida Arumingtyas; Lisdewi Muliati (Jurnal Akuntansi dan Keuangan Islam, 2019)
This study was conducted to examine indicators as a measured by inflation and interest rates to the Return On Asset (ROA) of Shariah Banking in Indonesia. Data analysis techniques used in this study is multiple linear regression analysis. Whereas the data used is secondary data, thus to determine the accuracy of model it is important to test some classical assumption underlined the regression model. The classical assumption testing used in this research contain of experiment, normality, multicolinearity, heteroskedatisitas and autocorrelation. The results showed that the rate of inflation and interest rate variables simultaneously affect significantly to Return On Asset (ROA). According to the t test result, it can conclude that inflation variables partially have effect to Return On Asset (ROA), whereas interest rates variables don’t have effect partially. Keywords: inflation, interest rates, ROA